CMOS Active Inductor Based Voltage Controlled Oscillator - Dhara P Patel; Shruti Oza; Rajesh A Thakker (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
A Tunable Active Inductor (TAI) based Voltage Controlled Oscillator (VCO) for Radio Frequency (RF) applications ranging from 670 MHz - 1.53 GHz is presented. A design of low phase noise and compact VCO is proposed. In order to lower the phase noise of VCO, its RF output power has been improved. The use of low voltage active in-ductor circuit reduces the power dissipation of VCO. The single ended CMOS active inductors with minimum number of transistors are used to consume less die area of VCO circuit. The low power dissipation of the circuit have high efficiency to generate output RF power. A supply independent variable current source tunes the VCO. The post layout design is simulated in Cadence spectreRF using TSMC 180 nm process libraries. The VCO circuit shows the phase noise variation from -124 to  - 126 dBc/Hz and an active area of 0.0049 mm2. The VCO core circuit, excluding output buffers, consumes 10 mW at 1.8 V supply voltage.